Stepwise evolution of Elk-1 in early deuterostomes - Saxton, Janice; Ferjentsik, Zoltan; Ducker, Charles; Shaw, Peter E. (Wiley, 2016)
Metazoans have multiple ETS paralogues with overlapping or indiscriminate biological functions. Elk- 1, one of three mammalian Ternary Complex Factors (TCFs), is a well-conserved, ETS domain-containing transcriptional regulator of mitogen-responsive genes that operates in concert with Serum Response Factor (SRF). Nonetheless, its genetic role remains unresolved because the elk-1 gene could be deleted from the mouse genome seemingly without adverse effect. Here we have explored the evolution of Elk-1 to gain insight into its conserved biological role. We identified antecedent Elk-1 proteins in extant early metazoans and used amino acid sequence alignments to chart the appearance of domains characteristic of human Elk-1. We then performed biochemical studies to determine whether putative domains apparent in the Elk-1 protein of a primitive hemichordate were functionally orthologous to those of human Elk-1. Our findings imply the existence of primordial Elk-1 proteins in primitive deuterostomes that could operate as mitogen-responsive ETS transcription factors but not as TCFs. The role of TCF was acquired later, but presumably prior to the whole genome duplications in the basal vertebrate lineage. Thus its evolutionary origins link Elk-1 to the appearance of mesoderm.